Job-Oriented CBT-Training Technology - Boyd, Susan; Exner, Debra (Association for Talent Development, 1998)
This Info-line explains the steps needed to provide a job-oriented approach to training plus follow-up training. It includes suggestions for adapting this approach for diverse groups and sample forms and check lists.